Education Change Strategy - Husna, Fitri Maulida (Jurnal Fokus Manajemen, 2024)
Change management is a systematic process of applying the knowledge, tools and resources needed to effect change in the people who will be affected by the process. Change management is also understood as an effort taken by managers to manage change effectively, which requires an understanding of issues of motivation, leadership, groups, conflict, communication and discipline. Thus change management should have a good strategy, according to the current situation and conditions. or will happen. Organizational change is one thing that cannot be avoided by public organizations. The dynamic organizational environment and the high demands of society for quality services make public organizations must be able to adapt to change. Strategic issues that are problems in education today include low quality attainment in terms of graduate productivity, factors related to value for money issues and educational accountability factors. Organizational Behavior includes a complex collection of ideologies, symbols, and core values that apply to a company and influence the way it does business. Sharpening organizational culture is a central task of effective strategic leadership.